Hubungan Adekuasi Hemodialisis, Risiko Malnutrisi, dan Tingkat Depresi dengan Kualitas Hidup Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisis di RSUD dr. H. Andi Abdurrahman Noor Kabupaten Tanah Bumbu - Erviani Erviani; Rijanti Abdurrachim; Mahpolah Mahpolah; Rosihan Anwar (HB PRESS, 2025)
Chronic Kidney Failure (CKD) continues to increase and requires long-term hemodialysis, impacting patients' physical, nutritional, and psychological status, as well as their quality of life. This study aims to determine the relationship between hemodialysis adequacy, malnutrition risk, and depression levels, and the quality of life of CKD patients at Dr. H. Andi Abdurrahman Noor Regional General Hospital in Tanah Bumbu Regency.This observational study used a cross-sectional design involving 34 hemodialysis patients at the time of the study. The variables studied included hemodialysis adequacy, malnutrition risk, depression levels, and quality of life. Data were analyzed using the Spearman Rank Correlation test at ? = 0.05.The majority of respondents were of productive age, female, retired, and had higher education. Furthermore, some respondents also had good hemodialysis adequacy, good nutritional status, mild depression, and a very good quality of life. There was a significant association between hemodialysis adequacy (p=0.019; r=0.401), malnutrition risk (p=0.001; r=0.530), and depression levels (p=0.014; r=0.416) and quality of life. This study shows that adequate hemodialysis, optimal nutritional status, and low depression improve patients' quality of life. It is recommended that nutritionists be placed in hemodialysis units as part of a multidisciplinary team to optimize nutrition, reduce the risk of PEW, and improve quality of life.